2004
DOI: 10.1086/381262
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Endophthalmitis

Abstract: Postoperative endophthalmitis remains a serious clinical problem in ophthalmology, with an incidence of approximately 0.5%. Prognosis is largely determined by the virulence of the offending organism. The Endophthalmitis Vitrectomy Study (EVS) was a prospective, randomized trial comparing various diagnostic and treatment modalities in cases of endophthalmitis that followed cataract surgery. The EVS found that vitrectomy was only beneficial for patients presenting with very poor visual acuity and that intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…A rapid antibiotic therapy is the only way of treatment. For this reason, an empiric antibiotic therapy done with wide spectrum drugs has to be started before the identification of the etiological agent [2,12]. On the contrary the use of steroid does not find a unanimous consensus [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A rapid antibiotic therapy is the only way of treatment. For this reason, an empiric antibiotic therapy done with wide spectrum drugs has to be started before the identification of the etiological agent [2,12]. On the contrary the use of steroid does not find a unanimous consensus [20].…”
Section: Discussionmentioning
confidence: 99%
“…This kind of endophthalmitis is one of the most serious and deleterious condition after the surgical treatment of cataract with an incidence of 0.13-0.7 % [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus epidermidis is the most common pathogen isolated in culture-proven endophthalmitis (60% of cases), Staphylococcus aureus, Streptococcus spp., and Enterococcus spp. are each found in 5%-10%, and other Gram-negative bacteria are found in 6% of cases [1]. Isolated microorganisms usually represent the preoperative, endogenous colonization of the patients' eyelids and conjunctivae, but might also originate from unusual exogenous sources, e.g., contaminated surgical material or ocular rinsing solution.…”
Section: Introductionmentioning
confidence: 99%
“…PVP-I is effective in treating bacterial conjunctivitis, as a postoperative antibacterial, for preoperative prophylaxis, in combination with antibiotics topically, for prophylaxis against ophthalmia neonatorum, and for various other ophthalmologic uses. [4][5][6][7][8][9][10] Despite the efficacy of PVP-I against various pathogens, research is ongoing as to the toxicity of PVP-I in ocular tissues. Naor and colleagues demonstrated that while 0.1% PVP-I is well tolerated on the corneal endothelium in-vivo, 1.0% is not.…”
Section: Introduction P Ovidone-iodine (Pvp-i) Is Widely Recognizedmentioning
confidence: 99%